SOS-induced DNA polymerases enhance long-term survival and evolutionary fitness - Yeiser, Bethany (National Academy of Sciences, 2002)
Escherichia coli encodes three SOS-induced DNA polymerases: pol II, pol IV, and pol V. We show here that each of these polymerases confers a competitive fitness advantage during the stationary phase of the bacterial life cycle, in the absence of external DNA-damaging agents known to induce the SOS response. When grown individually, wild-type and SOS pol mutants exhibit indistinguishable temporal growth and death patterns. In contrast, when grown in competition with wild-type E. coli, mutants lacking one or more SOS polymerase suffer a severe reduction in fitness. These mutants also fail to express the “growth advantage in stationary phase” phenotype as do wild-type strains, instead expressing two additional new types of “growth advantage in stationary phase” phenotype. These polymerases contribute to survival by providing essential functions to ensure replication of the chromosome and by generating genetic diversity.